Bioconversion of Oil Palm Empty Fruit Bunches into Lactic Acid via Lactobacillus acidophilus - Rahmath Abdulla; Eryati Derman; Sharmilah Balasubramaniam; Jualang Azlan Gansau; Anuj Kumar Chandel (Springer Nature, 2025)
The production of lactic acid (LA), a key precursor for poly-lactic acid (PLA) as a sustainable alternative to conventional plastics, is gaining significant industrial and environmental attention. This study evaluates the potential of utilizing oil palm empty fruit bunches (EFBs), an abundant lignocellulosic agro-industrial waste, for lactic acid production through fermentation. A separate hydrolysis and fermentation (SHF) process was employed using Lactobacillus acidophilus A1 ATCC 4356, chosen for its ability to optimize enzymatic hydrolysis and fermentation independently, thereby enhancing process efficiency. Fermentation conditions, including inoculum size, temperature and time, were systematically optimized to achieve maximum lactic acid yield. Under optimal conditions (35 °C, 10% (v/v) inoculum, 120 h), the process yielded 6.49 g/L of lactic acid, corresponding to an impressive 94% conversion efficiency. This high yield demonstrates the feasibility of EFBs as a low-cost, renewable feedstock for industrial-scale lactic acid production, reducing dependence on traditional sugar- or starch-based substrates. This study highlights the potential of SHF with L. acidophilus to transform agricultural residues into valuable biochemical, advancing the circular bioeconomy and waste valorization initiatives.